Edukasi Interaktif: Literasi Digital dan Etika Bermedia Sosial Bagi Peserta Didik Baru SMK Xaverius Palembang - Jevanda BS, Klaudius; Hermawan, Latius; Nurmansyah, Wawan; Fery Herdiyatmoko, Hendrik; Ninda Permata Nugraha, Fransiska (Lembaga Pengembangan Kinerja Dosen, 2026)
In today’s world, social media has become an everyday necessity for interacting and socializing with others, but it has both positive and negative effects, particularly on the younger generation. The roles of parents and educators are crucial in building digital resilience among the younger generation, such as the new students at SMK Xaverius Palembang. One solution is to provide early education to new students during the School Environment Orientation Program. The UKMC Community Service Team served as guest speakers, presenting material on digital literacy and social media ethics, along with real-life case studies, to the incoming students for the 2025/2026 academic year on Thursday, July 17, 2025, in the auditorium of SMK Xaverius Palembang. The method used involved an interactive educational approach, in which the team presented five questions related to online gambling, fake news, cyberbullying, explicit content, and ending human trafficking in the form of digital posters, and the students explained them. The team also provided real-life examples and explained the causes and effects. The purpose of this activity is to educate new students at SMK Xaverius Palembang to improve their understanding of digital literacy and social media ethics, and to encourage them to use social media more wisely. According to the research findings, the activity proceeded as planned, and the students were very enthusiastic about participating in the discussion and answering questions using digital posters.